Hybrid objective structured clinical examination (OSCE) for preclinical medical student in UPM: a lesson learnt from COVID-19 pandemic - Hassan, Haniza; Adam, Siti Khadijah; Mahayidin, Hasni; Mohamad Asri, Siti Fadziyah (Universiti Putra Malaysia, 2024)
The global lockdown caused by the COVID-19 pandemic in 2020 necessitated several modifications for objective structured clinical examination (OSCE) to be conducted virtually. Since the reopening of higher institutions post COVID-19 in the year 2022, the teaching and learning methods at Universiti Putra Malaysia (UPM) have reverted to either face-to-face or hybrid modes. Nevertheless, there were circumstances where an adaptation of the virtual OSCE method for a hybrid session had to be arranged, specifically for students who could not physically attend the examination. Therefore, in this commentary, we aim to share the experience of conducting a hybrid OSCE session for preclinical medical students at UPM. It also summarises the advantages and challenges faced by the students, examiners and examination committee, as well as future recommendations, should a similar situation arises in the future.